2017
DOI: 10.14236/jhi.v24i3.907
|View full text |Cite
|
Sign up to set email alerts
|

Effectively reducing amylase testing using computer order entry in the emergency department: quality improvement without eliminating physician choice

Abstract: Background Amylase and lipase, pancreatic biomarkers, are measured in acute pancreatitis diagnosis. Since amylase testing does not add diagnostic value, lipase testing alone is recommended. Despite new recommendations, many physicians and staff continue to test both amylase and lipase. Objective To reduce unnecessary diagnostic testing in acute pancreatitis. Methods The pre-checked amylase test within the Emergency Department's Computerised Provider Order Entry (CPOE) abdominal pain order set was changed to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…However, our finding of a high rate of super-fluous amylase/lipase testing that was mainly due to simultaneous amylase/lipase testing confirms the results of two recent US studies where 71% to 75% of patients had simultaneous amylase/lipase testings. 12,13 The American College of Gastroenterology guidelines and the American Gastroenterology Association technical review state that measuring both serum amylase and lipase in acute pancreatitis is not necessary. 8,9 Consistent with the guidelines, we found that it is rare to have a diagnostic amylase result simultaneously with a non-diagnostic lipase result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our finding of a high rate of super-fluous amylase/lipase testing that was mainly due to simultaneous amylase/lipase testing confirms the results of two recent US studies where 71% to 75% of patients had simultaneous amylase/lipase testings. 12,13 The American College of Gastroenterology guidelines and the American Gastroenterology Association technical review state that measuring both serum amylase and lipase in acute pancreatitis is not necessary. 8,9 Consistent with the guidelines, we found that it is rare to have a diagnostic amylase result simultaneously with a non-diagnostic lipase result.…”
Section: Discussionmentioning
confidence: 99%
“…13 Jaeger and colleges changed the default status of amylase test from checked to un-checked in the order set for abdominal pain; within a year, simultaneous amylase/lipase testing decreased by 87%. 12 Similarly, removing amylase from common order sets in electronic medical records reduced simultaneous amylase/lipase testing by 15% in a US university hospital 15 and decoupling amylase and lipase and removing amylase from order entry forms reduced simultaneous testing from 93% to 14% in a US trauma center. 16 It appears that similar quality-improvement initiatives at KFSHRC could be of benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplicate orders, unit errors, the use of free text, parameterization flaws, and poor usability of software are probably the root of many prescribing errors [5,6]. The results of a similar study revealed that changing the computerized ordering system could significantly reduce costs [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to flag how a tiny informatics intervention has an effect. The example in the paper is where a provider wishes to discourage the use of a test called amylase alongside a more specific test called lipase 8. The remit of this journal is to report the impact of the informatics; the issues over which tests to use in pancreatitis are beyond the scope of this journal and remain being discussed in the peer review literature, including a recent Cochrane Review 9…”
Section: Unchecking a Box Has An Effect Size – On Electronic Formsmentioning
confidence: 99%